Hubungan Antara Insiden Demam Berdarah Dengue (DBD) dan Faktor Sanitasi Lingkungan : Tinjauan Sistematik Review - Juliska, Shelly; Windusari, Yuanita; Novrikasari; Nur Alam Fajar (Health Information : Jurnal Penelitian, 2023)
Dengue hemorrhagic fever (DHF) is a vector-borne disease caused byflavivirus that  causes morbidity and death rates that are still quitehigh globally. This disease is influenced by many factors includingenvironmental factors that have a very close association with theincidence of DHF. Although there have been many previous studies thatanalyzed the relationship of environmental factors to the incidence ofDHF, the results are still inconsistent. This paper aims to analyze therelationship between the incidence of dengue fever and environmentalsanitation factors. The research design used the systematic reviewmethod. Articles are selected using the PRISMA (Preferred ReportingItems for Systematic Reviews and Meta Analysis) method  on the googlescholar search engine. The inclusion criteria in this writing arearticles published within the last 5 years, starting from 2019 – 2023with  the keyword "DHF and Environmental Sanitation, BivariateAnalysis", can be accessed in full, using  a cross-sectional studydesign  and relevant to the theme of writing. The results obtained were8 articles that met the criteria with environmental sanitation variablesrelated to mobility and population density as well as the location ofurban residences, waste disposal and management, water reservoirs,eradication of mosquito nests and the use of mosquito repellent, thepresence of water drainase system and behavior as social environmentalfactors. The conclusion of this study is that environmental variables,both physical, biological and social, have a significant relationshipwith the risk of dengue events. The difference in results in the studyis due only to the differences in parameters observed in the study.